2018
DOI: 10.19044/esj.2018.v14n27p297
|View full text |Cite
|
Sign up to set email alerts
|

Effets De l’Acide Naphtalène Acétique, Du Type De Substrat Et De La Grosseur Des Boutures Sur Le Bouturage De Tige De Pterocarpus Erinaceus Poir. (Fabaceae)

Abstract: This study, conducted in south-east Benin, aims to provide practical information on the optimal conditions for successful propagation of stem cuttings of Pterocarpus erinaceus Poir. (Fabaceae), a real alternative to its regeneration and domestication. A trial was conducted to evaluate the effect of different doses of Acid Naphthalene Acetate (ANA) (0; 500; 750; 1000 and 1500 mg/l), the type of substrate (black forest sand and fine sand) and the size of the cuttings used ([1.5-2] and [2.5-3] cm of diameter) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…These results are also similar to those obtained by [22], who showed that semi-woody cuttings pretreated with indole butyric acid (IBA), had the best rooting rates compared to the rooting rate of untreated cuttings. On the other hand, our results are different from those obtained by [23] Bodjrenou et al, 2018 who showed that NAA and IBA are ineffective in the rhizogenesis of Pterocarpus erinaceus. Identical behavior is reported in Lovoa trichilioides [24] and Dacryodes edulis [25].…”
Section: Discussioncontrasting
confidence: 99%
“…These results are also similar to those obtained by [22], who showed that semi-woody cuttings pretreated with indole butyric acid (IBA), had the best rooting rates compared to the rooting rate of untreated cuttings. On the other hand, our results are different from those obtained by [23] Bodjrenou et al, 2018 who showed that NAA and IBA are ineffective in the rhizogenesis of Pterocarpus erinaceus. Identical behavior is reported in Lovoa trichilioides [24] and Dacryodes edulis [25].…”
Section: Discussioncontrasting
confidence: 99%